Lo sviluppo delle discipline : Dall indistinzione alla complessità - Orefice, Paolo (Florence Firenze University Press, 2020)
The birth and development of disciplines, as organized knowledge that guides the interpretation of reality, are inscribed in the heritage of the knowledge of our species. These follow the triple regulating principles of the historical flux of the meanings of feeling and thinking: cognitive potential, mental processing, intangible and tangible products. The flow from the indistinct feeling of the origins evolves through the archaic forms of the magic thought; to the ancient forms of declarative thought up to the modern forms of demonstrative thought. The latter with the separation between disciplines does not recognize the interconnection inherent in reality, loses the scientific revolution character and generates the unsustainable human development on the planet. From the global interconnection experience of the contemporary world, a new paradigm comes to life: transdisciplinarity, whose epistemology recomposes the knowledge and reality s unity and diversity beyond the barriers between disciplines.
Italian
Keywords: disciplines development; disciplinary relations; knowledge paradigms; complexity; transdisciplinarity; relational intelligence